A semi-solid battery separator and method of making the same

CN121709859BActive Publication Date: 2026-10-27SINOMA LITHIUM BATTERY SEPARATOR CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411313734.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2026-10-27
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

[0005]本发明的主要目的在于提供一种半固态电池隔膜及其制备方法,以克服现有技术中半固态电池隔膜的浸润性较差、隔膜表面和电解质接触面积不均匀等问题

Benefits of technology

[0028]本发明半固态电池隔膜具有高浸润性,有效改善了电解液在隔膜中的渗透效果,使电解液能够更均匀地分布,从而减少了界面不稳定性的风险,因此,由本发明隔膜制备的电池具有较高的离子电导率和较好的循环稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005051518060000121
    Figure BDA0005051518060000121
Patent Text Reader

Abstract

The application provides a semi-solid battery diaphragm and a preparation method thereof. The diaphragm comprises a base film and a coating layer formed on at least one surface of the base film, and the coating layer comprises modified carbon nanotubes, ceramic particles, lithium salt and an auxiliary agent. The modified carbon nanotubes are obtained by polymerizing dopamine and attaching the dopamine to carbon nanotubes. The semi-solid battery diaphragm has high wettability, effectively improves the penetration effect of electrolyte in the diaphragm, enables the electrolyte to be more uniformly distributed, and thus reduces the risk of interface instability. Therefore, the battery prepared by using the diaphragm has high ionic conductivity and good cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium batteries, and specifically to a semi-solid battery separator and its preparation method. Background Technology

[0002] Semi-solid batteries combine the high safety of solid-state batteries with the excellent conductivity and ion conduction of liquid batteries, thus showing great practical potential.

[0003] Semi-solid-state batteries are characterized by high energy density and good safety. Among them, the separator, as one of the important and expensive key components of a semi-solid-state battery, has the function of separating the positive and negative electrode active materials, selectively allowing specific ions to pass through to form a conductive circuit, and at the same time, it must possess electronic insulation properties. In semi-solid-state batteries, the quality of the separator directly affects the battery's performance and lifespan.

[0004] In existing technologies, semi-solid battery separators exhibit poor wettability and uneven contact area between the separator surface and the electrolyte, which consequently affects the ionic conductivity of the separator and the stability of the battery. Therefore, further research on semi-solid battery separators is needed in this field. Summary of the Invention

[0005] The main objective of this invention is to provide a semi-solid battery separator and its preparation method, so as to overcome the problems of poor wettability and uneven contact area between the separator surface and the electrolyte in the prior art.

[0006] To achieve the above objectives, the present invention provides a semi-solid battery separator, comprising a base film and a coating layer formed on at least one surface of the base film, the coating layer comprising modified carbon nanotubes, ceramic particles, lithium salt and additives; the modified carbon nanotubes are obtained by polymerizing dopamine and attaching it to the carbon nanotubes.

[0007] In one embodiment of the semi-solid battery separator of the present invention, the coating layer includes a first coating layer (coating slurry) and a second coating layer (semi-solid electrolyte slurry), wherein the first coating layer includes carbon nanotubes, ceramic particles and additives, and the second coating layer includes lithium salt.

[0008] In one embodiment of the semi-solid battery separator of the present invention, the first coating layer is formed between at least one surface of the base film and the second coating layer; or, the second coating layer is formed between at least one surface of the base film and the first coating layer.

[0009] In one embodiment of the semi-solid battery separator of the present invention, the lithium salt is selected from one of LiBH4, LiPF6, LiTFSI, LiClO4, LiBF4, and LiAsF4.

[0010] In one embodiment of the semi-solid battery separator of the present invention, the method for preparing the modified carbon nanotubes includes: mixing a dispersion of carbon nanotubes in water with dopamine and stirring to obtain modified carbon nanotubes; the mass ratio of the carbon nanotubes to the dopamine is (1-2):(2-1).

[0011] In one embodiment of the semi-solid battery separator of the present invention, the length of the carbon nanotube is 8-10 nm and the aspect ratio is 2.6-20; and / or the particle size of the ceramic particles is 20-50 nm; and / or the mass ratio of the modified carbon nanotube to the ceramic particles is (10-30):(90-70).

[0012] In one embodiment of the semi-solid battery separator of the present invention, the additives include polyvinylidene fluoride powder, dispersant, wetting agent, binder and solvent.

[0013] To achieve the above objectives, the present invention also provides a method for preparing a semi-solid battery separator, comprising the following steps:

[0014] Step 1A: Mix modified carbon nanotubes, ceramic particles and additives to obtain a first coating slurry, and coat the first coating slurry onto the base film to form a first coating layer on the base film;

[0015] Step 2A: Mix lithium salt, organic solvent and additive to obtain second coating slurry, and coat the second coating slurry onto the first coating layer to form a second coating layer on the first coating layer;

[0016] The modified carbon nanotubes are obtained by polymerizing dopamine and attaching it to carbon nanotubes.

[0017] To achieve the above objectives, the present invention further provides a method for preparing a semi-solid battery separator, comprising the following steps:

[0018] Step 1B: Mix lithium salt, organic solvent and additive to obtain second coating slurry, and coat the second coating slurry onto the base film to form a second coating layer on the base film;

[0019] Step 2B: Mix modified carbon nanotubes, ceramic particles and additives to obtain a first coating slurry, and coat the first coating slurry onto the second coating layer to form the first coating layer on the second coating layer;

[0020] The modified carbon nanotubes are obtained by polymerizing dopamine and attaching it to carbon nanotubes.

[0021] To achieve the above objectives, the present invention provides a method for preparing a semi-solid battery separator, comprising the following steps:

[0022] Step 1C: The modified carbon nanotubes, ceramic particles and additives are mixed to obtain the first coating slurry;

[0023] Step 2C: Mix lithium salt, organic solvent and additives to obtain the second coating slurry;

[0024] Step 3C: Mix the first coating layer slurry and the second coating layer slurry, and coat them onto the base film to form a coating layer on the base film.

[0025] In one embodiment of the method for preparing the semi-solid-state battery separator of the present invention, the method for preparing the modified carbon nanotubes includes:

[0026] Carbon nanotubes were dispersed in water to obtain a dispersion, which was then mixed with dopamine, stirred, and washed with water to obtain modified carbon nanotubes.

[0027] The beneficial effects of this invention are as follows:

[0028] The semi-solid battery separator of this invention has high wettability, which effectively improves the penetration effect of electrolyte in the separator and allows the electrolyte to be distributed more evenly, thereby reducing the risk of interfacial instability. Therefore, the battery prepared by the separator of this invention has high ionic conductivity and good cycle stability. Detailed Implementation

[0029] The present invention will be further described in detail below with reference to specific embodiments. The embodiments given are only for illustrating the present invention and are not intended to limit the scope of the present invention. The embodiments provided below can serve as a guide for those skilled in the art to make further improvements and do not constitute a limitation on the present invention in any way. Unless otherwise stated, the raw materials, reagents, devices, instruments, and equipment used in the embodiments of the present invention can all be obtained commercially.

[0030] The present invention provides a semi-solid battery separator, comprising a base film and a coating layer formed on at least one surface of the base film, the coating layer comprising modified carbon nanotubes, ceramic particles, lithium salt and additives; the modified carbon nanotubes are obtained by polymerizing dopamine and attaching it to the carbon nanotubes.

[0031] The coating of the semi-solid battery separator of this invention incorporates dopamine-modified carbon nanotubes, which can significantly improve the hydrophilicity of the separator, allowing the electrolyte to penetrate into the interior of the separator more quickly, thereby making the electrolyte more evenly distributed and reducing the risk of interfacial instability.

[0032] In this invention, dopamine molecules can be selected from polydopamine (PDA) formed by oxidative polymerization. The adhesive properties of PDA allow it to coat the surface of carbon nanotubes. Furthermore, the phenolic hydroxyl and amino functional groups in the dopamine molecules can chemically react with the functional groups (carboxyl and hydroxyl groups) on the surface of the carbon nanotubes. Therefore, the dopamine and carbon nanotubes of this invention have a strong interaction force, which not only enhances the stability of the membrane structure and improves the strength of the internal structure, but also improves the interfacial stability of the membrane. This allows the electrolyte to penetrate the membrane more quickly and uniformly, reducing resistance.

[0033] This invention does not impose any particular limitation on the base film; any commonly used base film in the art may be used. In one embodiment, the base film is a polyolefin base film, such as polyethylene or polypropylene, and the thickness of the base film is, for example, 3.5–9 μm. The coating layer is formed on at least one surface of the base film, and may be formed on one or both surfaces of the base film. The coating layer is formed by applying a coating slurry to the base film, and the coating layer (i.e., the coating slurry) includes modified carbon nanotubes, ceramic particles, lithium salts, and additives.

[0034] In one embodiment, the coating layer is a single-layer coating, that is, formed by coating in one step, and the coating layer thickness is, for example, 0.1 to 6 μm.

[0035] In another embodiment, the coating layer is prepared by:

[0036] Step 1C: The modified carbon nanotubes, ceramic particles and additives are mixed to obtain the first coating slurry;

[0037] Step 2C: Mix lithium salt, organic solvent and additives to obtain the second coating slurry;

[0038] Step 3C: Mix the first coating layer slurry and the second coating layer slurry, and coat them onto the base film to form the coating layer on the base film.

[0039] In one embodiment, after coating, a drying process is performed to remove solvents and moisture, allowing the coating to cure. The drying temperature is, for example, 100–150°C, and the drying time is, for example, 1–10 minutes.

[0040] In one embodiment, the coating layer comprises two layers: a first coating layer and a second coating layer. The first coating layer comprises carbon nanotubes, ceramic particles, and additives, and the second coating layer comprises a lithium salt. The thickness of the first coating layer can be 0.1–4 μm, and the thickness of the second coating layer can also be 0.1–4 μm. The first coating layer can be disposed between the base film and the second coating layer, or the second coating layer can be disposed between the base film and the first coating layer. Compared to coating a single layer with the second coating layer disposed between the base film and the first coating layer, disposing the first coating layer between the base film and the second coating layer results in better membrane wettability, allowing the electrolyte to penetrate into the membrane more quickly.

[0041] In another embodiment, the method for preparing the membrane in which the first coating layer is disposed between the base film and the second coating layer can be as follows:

[0042] Step 1A: Mix modified carbon nanotubes, ceramic particles and additives to obtain a first coating slurry, and coat the first coating slurry onto the base film to form a first coating layer on the base film;

[0043] Step 2A: Mix lithium salt, organic solvent and additive to obtain second coating slurry, and coat the second coating slurry onto the first coating layer to form a second coating layer on the first coating layer.

[0044] In another embodiment, the method for preparing a membrane in which a second coating layer is disposed between a base film and a first coating layer can be as follows:

[0045] Step 1B: Mix lithium salt, organic solvent and additive to obtain second coating slurry, and coat the second coating slurry onto the base film to form a second coating layer on the base film;

[0046] Step 2B: The modified carbon nanotubes, ceramic particles and additives are mixed to obtain a first coating slurry. The first coating slurry is then coated onto the second coating layer to form the first coating layer on the second coating layer.

[0047] In the second coating slurry, the lithium salt is a solid electrolyte material selected from one of LiBH4, LiPF6, LiTFSI, LiClO4, LiBF4, and LiAsF4, the organic solvent is, for example, ethylene carbonate EC, and the additive is, for example, ethylene carbonate VC.

[0048] In one embodiment, an appropriate amount of dispersant, thickener, and wetting agent may be added to the second coating slurry, and the mixture is stirred and ball-milled to ensure uniform mixing of the substances and obtain the second coating slurry.

[0049] In another embodiment, the second coating slurry contains 1-5 wt% lithium salt, 70-90 wt% organic solvent, 1-5 wt% additive, 0.1-5 wt% dispersant, 0.1-3 wt% thickener, and 0.01-1 wt% wetting agent.

[0050] This invention does not specifically limit the types of dispersants, thickeners, wetting agents, etc., and these additives are all conventional additives in the art.

[0051] In one embodiment, the method for preparing modified carbon nanotubes includes: mixing a dispersion of carbon nanotubes in water with dopamine and stirring to obtain modified carbon nanotubes. More specifically, it can be: mixing carbon nanotubes with water to disperse the carbon nanotubes in the water, the mixing process may be ultrasonically treated, then mixing the carbon nanotube dispersion with dopamine and stirring for, for example, 12 hours or more, more specifically 24 hours or more, so that dopamine polymerizes and adheres to the surface of the carbon nanotubes. To remove unreacted dopamine and other impurities, the reaction mixture can be added to water, the impurities can be dissolved by thorough stirring, and then solid-liquid separation can be performed. Taking advantage of the high solubility of impurities in water, the pure solid sample PDA-CNTs (dopamine-modified carbon nanotubes) can be successfully separated. In the membrane formed by dopamine-modified carbon nanotubes, the polar groups such as hydroxyl and amino groups on dopamine can coordinate with lithium ions, and the resulting structure promotes the formation of a three-dimensional structure and forms more transport channels.

[0052] In one embodiment, the length of the carbon nanotubes of the present invention is 8–20 nm, more preferably 8–10 nm, smaller than the pore size of the base membrane (e.g., 30–40 nm). The diameter of the carbon nanotubes is 1–3 nm, and the aspect ratio is 2.6–20, more preferably 2.6–10 or 3.3–20, wherein the aspect ratio AR = L (length) / D (diameter). When the length of the carbon nanotubes is too long, they will aggregate and become entangled, affecting the membrane performance. The carbon nanotubes of the present invention have a specific aspect ratio, which can form a stable three-dimensional network structure in the pores inside the base membrane, thereby guiding the electrolyte flow, reducing flow resistance, and further improving the electrolyte wetting effect. In another embodiment, the mass ratio of carbon nanotubes to dopamine is (1–2):(2–1), more preferably 1:1.

[0053] The present invention does not specifically limit the type of ceramic particles, which can be one or more of alumina, magnesium oxide, titanium dioxide, and silicon dioxide. In one embodiment, the particle size of the ceramic particles is greater than or equal to 20 nm and less than 50 nm, and further, it can be 20 to 35 nm. The particle size of the ceramic particles is smaller than the pore size of the base film, so as to ensure porosity, ensure the unobstructed ion channels, and avoid blockage.

[0054] In one embodiment, the mass ratio of modified carbon nanotubes to ceramic particles is (10-30):(90-70).

[0055] In one embodiment, the additives include polyvinylidene fluoride (PVDF) powder, dispersants, wetting agents, binders, and solvents. This invention does not particularly limit the types of dispersants, wetting agents, binders, and solvents; conventionally selected materials in the art are acceptable. This invention also does not particularly limit the amount of each additive; they can be selected as needed.

[0056] Therefore, the diaphragm of this invention exhibits good wetting properties, which can improve the problem of electrolyte interface instability. The wetting properties are mainly reflected in two aspects: first, the modified carbon nanotubes enhance the hydrophilicity of the diaphragm coating, allowing the electrolyte to penetrate into the diaphragm more quickly; second, the carbon nanotubes have a specific aspect ratio, which allows for more precise matching with the pore structure within the diaphragm, further improving the electrolyte wetting effect. Interface instability is mainly reflected in two aspects: first, the contact area between the diaphragm surface and the electrolyte is uneven; second, the pore structure or surface properties of the diaphragm material are uneven.

[0057] The technical solution of the present invention will be further described in detail below with reference to specific embodiments.

[0058] Example 1

[0059] 1. Coating preparation

[0060] 1.1 Preparation of Dopamine-Modified Carbon Nanotubes

[0061] Polymerization process: CNTs (length: 8-10 nm; diameter: 1-3 nm; aspect ratio: 2.6-10) were effectively dispersed in deionized water using an ultrasonic cleaner. An appropriate amount of dopamine (CNTs: dopamine (mass ratio) = 1:1) was added to the CNT dispersion, and the mixture was continuously stirred with a magnetic stirrer for about 24 hours to ensure that the dopamine was fully polymerized and attached to the CNT surface. Sample washing process: In order to remove unreacted dopamine and other impurities, the polymerization product was added to a sufficient amount of deionized water. The impurities were dissolved by thorough stirring, and then centrifuged. Taking advantage of the high solubility of impurities in water, the pure solid sample PDA-CNTs (dopamine-modified carbon nanotubes) was successfully separated.

[0062] 1.2 Preparation of Coating Slurry (First Coating Layer Slurry)

[0063] PDA-CNTs (dopamine-modified carbon nanotubes) and ceramic particles (20–35 nm in diameter) were mixed at a mass ratio of 1:9 to form composite particles. Then, appropriate amounts of PVDF powder, dispersant, wetting agent, binder, and solvent were added to prepare a coating slurry.

[0064] 2. Coating layer application

[0065] The coating slurry is evenly applied to the surface of the polyolefin-based film. A drying process is then performed to remove solvents and moisture, allowing the coating to cure.

[0066] 3. Preparation of semi-solid electrolyte slurry (second coating layer slurry)

[0067] Solid electrolyte material LiBH4 is mixed with organic solvent (ethylene carbonate EC) and additive (ethylene carbonate VC) in a certain proportion, and appropriate proportions of dispersant, thickener, wetting agent, etc. are added. The mass ratio of the solid electrolyte material, organic solvent, additive, dispersant, thickener and wetting agent is 4:90:3:2:1:0.1. The mixture is uniformly dispersed by stirring, ball milling and other methods to form a semi-solid electrolyte slurry.

[0068] 4. Semi-solid electrolyte coating

[0069] The prepared semi-solid electrolyte slurry is uniformly coated onto the pretreated base film from step 2. The coated base film is then dried (at 130°C for 5 minutes) to remove solvents and moisture, allowing the semi-solid electrolyte coating to cure.

[0070] Example 2

[0071] 1. Coating preparation

[0072] 1.1 Preparation of Dopamine-Modified Carbon Nanotubes

[0073] Polymerization process: CNTs (length: 10-20 nm; diameter: 1-3 nm; aspect ratio: 3.3-20) were effectively dispersed in deionized water using an ultrasonic cleaner. An appropriate amount of dopamine (CNTs: dopamine = 1:1) was added to the CNT dispersion, and the mixture was continuously stirred with a magnetic stirrer for about 24 hours to ensure that the dopamine was fully polymerized and attached to the CNT surface. Sample washing process: In order to remove unreacted dopamine and other impurities, the polymerization product was added to a sufficient amount of deionized water. The impurities were dissolved by thorough stirring, and then centrifuged. Taking advantage of the high solubility of impurities in water, the pure solid sample PDA-CNTs (dopamine-modified carbon nanotubes) was successfully separated.

[0074] 1.2 Preparation of coating slurry

[0075] The preparation of the coating slurry was the same as that in Example 1.

[0076] 2. Coating layer application

[0077] The coating slurry is evenly applied to the surface of the base film. A drying process is then performed to remove solvents and moisture, allowing the coating to cure.

[0078] 3. Preparation of semi-solid electrolytes

[0079] The preparation method of the semi-solid electrolyte is the same as that in Example 1.

[0080] 4. Semi-solid electrolyte coating

[0081] The coating method for the semi-solid electrolyte is the same as that in Example 1.

[0082] Example 3

[0083] 1. Coating preparation

[0084] 1.1 Preparation of Dopamine-Modified Carbon Nanotubes

[0085] Polymerization process: CNTs (length: 8-10 nm; diameter: 1-3 nm; aspect ratio: 2.6-10) were effectively dispersed in deionized water using an ultrasonic cleaner. An appropriate amount of dopamine (CNTs: dopamine = 1:1) was added to the CNT dispersion, and the mixture was continuously stirred with a magnetic stirrer for about 24 hours to ensure that the dopamine was fully polymerized and attached to the CNT surface. Sample washing process: In order to remove unreacted dopamine and other impurities, the polymerization product was added to a sufficient amount of deionized water. The impurities were dissolved by thorough stirring, and then centrifuged. Taking advantage of the high solubility of impurities in water, the pure solid sample PDA-CNTs (dopamine-modified carbon nanotubes) was successfully separated.

[0086] 1.2 Preparation of coating slurry

[0087] PDA-CNTs (dopamine-modified carbon nanotubes) and ceramic particles (35-50 nm in diameter) were mixed at a mass ratio of 1:9 to form composite particles. Then, appropriate amounts of PVDF powder, dispersant, wetting agent, binder, and solvent were added to prepare a coating slurry.

[0088] 2. Coating layer application

[0089] The coating slurry is evenly applied to the surface of the base film. A drying process is then performed to remove solvents and moisture, allowing the coating to cure.

[0090] 3. Preparation of semi-solid electrolytes

[0091] The preparation method of the semi-solid electrolyte is the same as that in Example 1.

[0092] 4. Semi-solid electrolyte coating

[0093] The coating method of the semi-solid electrolyte is the same as that in Example 1.

[0094] Example 4

[0095] 1. Preparation of Coating Layer

[0096] 1.1 Preparation of Dopamine-Modified Carbon Nanotubes

[0097] The preparation of the dopamine-modified carbon nanotubes is the same as the preparation method in Example 1.

[0098] 1.2 Preparation of Coating Slurry

[0099] The preparation of the coating slurry is all the same as the preparation method in Example 1.

[0100] 2. Preparation of Semi-Solid Electrolyte

[0101] The preparation of the semi-solid electrolyte is the same as the preparation method in Example 1.

[0102] 3. Blending of Semi-Solid Electrolyte and Coating Slurry

[0103] The semi-solid electrolyte and the coating slurry are mixed at a mass ratio of 1:1, and are uniformly dispersed by methods such as stirring and ball milling to form a homogeneous slurry.

[0104] 4. Coating

[0105] The prepared slurry is uniformly coated on a polyolefin base membrane, and the coated base membrane is subjected to a drying treatment (at 130°C for 5 min) to remove the solvent and moisture and cure the coating layer.

[0106] Example 5

[0107] 1. Preparation of Coating Layer

[0108] 1.1 Preparation of Dopamine-Modified Carbon Nanotubes

[0109] The preparation of the dopamine-modified carbon nanotubes is the same as the preparation method in Example 1.

[0110] 1.2 Preparation of Coating Slurry

[0111] The preparation of the coating slurry is all the same as the preparation method in Example 1.

[0112] 2. Preparation of Semi-Solid Electrolyte

[0113] The preparation of the semi-solid electrolyte is the same as the preparation method in Example 1.

[0114] 3. Coating of Semi-Solid Electrolyte

[0115] The prepared semi-solid electrolyte slurry was uniformly coated onto a polyolefin-based membrane. The coated membrane was then dried (at 130°C for 5 minutes) to remove solvents and moisture, allowing the semi-solid electrolyte coating to cure.

[0116] 4. Coating with slurry

[0117] The coating slurry is evenly applied to the surface of the base film treated in step 3. A drying process is then performed to remove solvents and moisture, allowing the coating to cure.

[0118] Comparative Example 1

[0119] 1. Preparation of coating slurry

[0120] CNTs (unmodified carbon nanotubes, length: 10–20 nm; diameter: 1–3 nm; aspect ratio: 2.6–10) were mixed with ceramic particles (particle size: 20–35 nm) at a mass ratio of 1:9 to form composite particles. Subsequently, appropriate amounts of PVDF powder, dispersant, wetting agent, binder, and solvent were added to prepare a coating slurry.

[0121] 2. Coating layer application

[0122] The coating slurry is evenly applied to the surface of the base film. A drying process is then performed to remove solvents and moisture, allowing the coating to cure.

[0123] 3. Preparation of semi-solid electrolytes

[0124] The preparation method of the semi-solid electrolyte is the same as that in Example 1.

[0125] 4. Semi-solid electrolyte coating

[0126] The coating method for the semi-solid electrolyte is the same as that in Example 1.

[0127] Comparative Example 2

[0128] 1. Preparation of coating slurry

[0129] Ceramic particles (particle size 20-35 nm) are mixed with appropriate amounts of PVDF powder, dispersant, wetting agent, binder and solvent to prepare a coating slurry.

[0130] 2. Coating layer application

[0131] The coating slurry is evenly applied to the surface of the base film. A drying process is then performed to remove solvents and moisture, allowing the coating to cure.

[0132] 3. Preparation of semi-solid electrolytes

[0133] The preparation method of the semi-solid electrolyte is the same as that in Example 1.

[0134] 4. Semi-solid electrolyte coating

[0135] The coating method for the semi-solid electrolyte is the same as that in Example 1.

[0136] The separators prepared in the above embodiments and comparative examples were assembled into batteries, and the performance of each battery was tested. The battery assembly sequence was as follows: using a CR2016 battery case, the assembly sequence was: negative electrode case - negative electrode (lithium sheet) - semi-solid electrolyte - lithium-ion battery separator - positive electrode - gasket - positive electrode case. Specific test data are shown in Table 1.

[0137] Table 1:

[0138]

[0139] As shown in Table 1, the contact angles of the electrolytes in Examples 1-5 of this application in air are 15-30°, indicating that dopamine-modified carbon nanotubes can significantly improve the hydrophilicity of the membrane, allowing the electrolyte to penetrate into the membrane more quickly, and resulting in superior surface wettability between the membrane and the electrolyte. Furthermore, a suitable aspect ratio of the carbon nanotubes can form a stable three-dimensional network structure within the membrane pores, which not only optimizes the uniformity of the pore size but also reduces the air permeability, giving the membrane higher ionic conductivity and lower thermal shrinkage.

[0140] Optionally, when the length of the carbon nanotube is 8-10 nm, the diameter is 1-3 nm, and the aspect ratio is 2.6-10, it matches the pore size of the membrane uniformly, effectively improving the membrane's air permeability, and exhibiting a lower ionic conductivity and a higher thermal shrinkage rate.

[0141] Optionally, when the particle size of the ceramic particles is 20-35 nm, it matches the pore size of the diaphragm uniformly, effectively improving the air permeability of the diaphragm, so that the diaphragm has better structural stability and higher thermal shrinkage rate.

[0142] Optionally, a membrane prepared by coating a first coating slurry onto the surface of a base membrane and then coating a second coating slurry onto the surface of the first coating layer has a larger number of effective contact sites at the interface between the membrane and the electrolyte compared to a membrane prepared by mixing a semi-solid electrolyte with a coating slurry and then coating it. This results in a lower electrolyte contact angle and a higher ionic conductivity.

[0143] Optionally, a separator prepared by coating a first coating slurry onto the surface of a base film and then coating a second coating slurry onto the surface of the first coating layer increases the effective contact area between the separator and the electrolyte compared to a separator prepared by first coating the base film with the second coating slurry and then coating the first coating slurry. This reduces the electrolyte contact angle and improves the ionic conductivity of the separator.

[0144] Comparative Example 1 uses unmodified carbon nanotubes, which reduces the number of polar groups (hydroxyl, amino, etc.) on the surface of the carbon nanotubes, thereby reducing the number of coordination with lithium ions, resulting in a significant increase in the contact angle of the electrolyte compared to Example 2.

[0145] Furthermore, in Comparative Example 2, the absence of carbon nanotubes further reduces the wettability of the membrane, decreases the porosity of the coating layer, and significantly reduces the diffusion efficiency of ions, thereby significantly reducing the ionic conductivity.

[0146] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A semi-solid battery separator, characterized in that, It includes a base film, a first coating layer and a second coating layer, wherein the first coating layer is formed between at least one surface of the base film and the second coating layer; The first coating layer comprises modified carbon nanotubes, ceramic particles, and additives, and the second coating layer comprises lithium salt; The modified carbon nanotubes are obtained by polymerizing dopamine and attaching it to the surface of carbon nanotubes. The preparation method of the modified carbon nanotubes includes: mixing and stirring a dispersion of carbon nanotubes in water with dopamine to obtain the modified carbon nanotubes. The carbon nanotubes have a length of 8-10 nm and an aspect ratio of 2.6-20, the ceramic particles have a particle size of 20-50 nm, and the mass ratio of the modified carbon nanotubes to the ceramic particles is (10-30):(90-70). The lithium salt is selected from one of LiBH4, LiPF6, LiTFSI, LiClO4, LiBF4, and LiAsF6.

2. The semi-solid battery separator according to claim 1, characterized in that, The mass ratio of the carbon nanotubes to the dopamine is (1~2):(2~1).

3. The semi-solid battery separator according to claim 1, characterized in that, The additives include polyvinylidene fluoride powder, dispersants, wetting agents, and binders.

4. A method for preparing a semi-solid battery separator, characterized in that, Includes the following steps: Step 1A: Mix modified carbon nanotubes, ceramic particles and additives to obtain a first coating slurry, and coat the first coating slurry onto the base film to form a first coating layer on the base film; Step 2A: Mix lithium salt, organic solvent and additive to obtain second coating slurry, and coat the second coating slurry onto the first coating layer to form a second coating layer on the first coating layer; The modified carbon nanotubes are obtained by polymerizing dopamine and attaching it to the surface of carbon nanotubes. The method for preparing the modified carbon nanotubes includes: mixing a dispersion of carbon nanotubes in water with dopamine and stirring to obtain the modified carbon nanotubes. The carbon nanotubes have a length of 8-10 nm and an aspect ratio of 2.6-20, the ceramic particles have a particle size of 20-50 nm, and the mass ratio of the modified carbon nanotubes to the ceramic particles is (10-30):(90-70). The lithium salt is selected from one of LiBH4, LiPF6, LiTFSI, LiClO4, LiBF4, and LiAsF6.

Citation Information

Patent Citations

  • Functionalized polyolefin composite diaphragm and preparation method and application thereof

    CN111725466A

  • Composite diaphragm modified by core-shell nanotube type structure material as well as preparation method and application of composite diaphragm

    CN115051107A